The Sami Theatre from Kauotokeino: On the Trace of Nomads - Sibińska, Maria (Przegląd Wschodnioeuropejski, 2018)
Beaivváš Sámi Našunálateáhter from Kautokeino (Norway) is an institutional theatre with Sami (Lappish) as the main stage language. Sami institutional theatres in Scandinavia have a relatively brief history which reflects the tension between the Sami people’s sociopolitical aspirations and Sami theatre artists’ freedom of expression. The theatre from Kautokeino is based upon a robust tradition (e.g. such pre-theatrical modes as the yoik, the art of storytelling, the shamanistic séance), and at the same time it is open to impulses from other cultures and theatrical traditions (both European and non-European). The article takes its point of departure in a postmodern concept of nomadism (Deleuze, Guattari, Braidotti, Islam). It focuses on the nomadic as the impetus and the driving force behind the Beaivváš Sámi Našunálateáhter. The nomadic, however, is understood not only as a reference to the Sami cultural heritage, but as an artistic practice based upon the reaction against aesthetically, historically, politically and socially rigid intellectual patterns. The practice is manifested, inter alia, in transgressions of established genres and aesthetic categories, multilingualism and cultural interferences.